Nanohybrid Catalyst based on Carbon Nanotube : A Step-By-Step Guideline from Preparation to Demonstration - Das, Rasel (Springer International Publishing : Imprint: Springer, 2017)
This book introduces carbon nanotubes as a matrix for efficient nanohybrid catalysis. The preparation and use of such materials in ultra-grade water purification is described. Simple chemical methods for purification and functionalization of carbon nanotubes prior to their use is also detailed. The author also discusses the potential use of nanotube-based nanobiohybrid catalysts in the removal of organic pollutants.
Keywords: Materials science.; Water quality.; Water pollution.; Catalysis.; Nanotechnology.; elektronické knihy; electronic books